Java GUI Programming - Rich, Eric ([S.l.] : KLS Corporation, 2001)
Learning how to develop graphical application using the powerful Java language.
Level 1. Introduction to GUI programming, getting started whith AWT, getting started with swing - level 2. layout management, event handling - level 3. text components, general components, tables - level4. growing trees, dialogs and POP-UPS, graphical programming, eriting applets